Analysis of Fraud Actions In Village Financial Management: Case Study of Maikor Village, North South Aru District, Aru Islands Regency - Maria Debora Arens; Stivan Harry Uniberua (Accounting Research Unit (ARU Journal), 2022)
This study aims to analyze acts of fraud, planning and accountability in village finances in Maikor Village, North South Aru District, Aru Islands Regency. Indonesia Corruption Watch (ICW) noted in the first semester of 2021 that the Village Government was the biggest perpetrator of corruption cases in Indonesia because the Anti-Corruption Behavior Index (IPAK) in Indonesia was 3.88 while the Anti-Corruption Behavior Index in rural areas reached 3.83. in 2021 so that village financial management has been regulated in Ministerial Regulation No. 37 of 2007 concerning Guidelines for Village Financial Management. This type of research is a descriptive qualitative research with a purposive sampling approach. The results in this study indicate that there are fraudulent acts that occur in village finances carried out by the village government in the 2010-2015 period with acts of misappropriation of funds and corruption of village finances. Thus, better prevention and inspection of village financial reports is needed so that fraud does not occur in village finances